(untitled) (Research, Society and Development, 2021)
Objective: Analyze the filling in the antimicrobial request form of the Intensive Care Unit in an oncology reference hospital in the state of Pará. Methods: This was a quantitative and retrospective study by collecting data from the restricted use antimicrobials request form, developed in the Intensive Care Unit of Hospital Ophir Loyola. Forms analyzed were from August to December 2018 in the file of the Hospital Infection Control Committee. Data obtained were organized in a database in Microsoft Excel® software, for descriptive statistical application, and the results were categorized and presented in a box and tables. Results: Of the 469 forms analyzed, 125 belonged to the month of August (27%), 96 (20%) September, 79 (17%) October, 96 (20%) November (20%) and 73 (16%) December. Meropenem was the most prescribed medication in the first three months (16%, 21.90% and 20.30%), in November, vancomycin was the most dispensed (11.5%) and, in December, piperacillin-tazobactam (tazocin - 20.5%). Regarding non-conformities, there is no form with the item “pharmaceutical form”. There were missing information on indication of use, data on the isolated infectious agent and omission of information on “progress of the requested microbiological study”. The indication for use was comprised between empirical and specific therapy. Conclusion: Thus, it is necessary to adjust the antimicrobial request form, inserting complementary data for greater patient safety and better prescription, promoting their rational use.